Evaluación de una planta piloto para el tratamiento de aguas residuales ordinarias por medio de un filtro percolador con relleno de esponjas colgantes de flujo descendente (DHS) como postratamiento de un efluente de sedimentador primario - Mora, Erick Centeno; Ugalde Herra, José Luis; Rodríguez Cambronero, Diego (Universidad de Costa Rica, 2017)
This research assessed the operation of a trickling filter filled with sponge media of polyurethane for the posttreatment of a primary clarifier effluent. This technology is known as Downflow Hanging Sponge (DHS). The treatment process was completed by a secondary clarifier (SS). The system DHS + SS was monitored for more than a year (inflow of the DHS and outflow of the SS), varying the hydraulic retention time (HRT) and following its performance for the organic matter removal.The system had his best behavior for a HRT of 2,8 hours, for an organic volumetric loading rate between 0,60 to 0,80 kgDBO/m3-d. For that condition, the system achieved the limits of BOD and COD established in the Costa Rican regulation in 100% of time, although the local limit for the parameter of the TSS was not reached in 25% of time. It is presumed that the system had some troubles at the level of the secondary clarifier, producing a sludge washing-out that jeopardized the final effluent quality.It is recommended to extend the scale of the DHS system, using a real wastewater treatment plant and upgrading the design for the distribution system at the inlet and for the secondary clarifier.